if y=x^(x^3), then dy/dx= a.) x^(x^3 +2) (2+3lnx) b.) x^(x^3+2) c.) 4x^(x^3+2) d.) x^3 (l+3lnx) e.) (lnx)x^(x^3)
Follow Math Help Forum on Facebook and Google+
Originally Posted by andyaddition if y=x^(x^3), then dy/dx= a.) x^(x^3 +2) (2+3lnx) b.) x^(x^3+2) c.) 4x^(x^3+2) d.) x^3 (l+3lnx) e.) (lnx)x^(x^3) Re-write the function: Use chain rule. For the derivation of the exponent you have to use the product rule. The solution is a).
Originally Posted by andyaddition if y=x^(x^3), then dy/dx= a.) x^(x^3 +2) (2+3lnx) Should be x^(x^3 +2) (1+3lnx)
yes thank you very much
View Tag Cloud